THE HYBRID LEARNING MODEL; A TEACHER STRATEGIES IN LEARNING MANAGEMENT DURING PANDEMIC - Rosi, Fathor; Abdurrahman, Abdurrahman; Wahyuni, Winda (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
The purpose of this study is to explain the Hybrid learning, learning management model during the Covid 19 Pandemic Period at Nurul Jadid University with a focus on management, learning planning, and evaluation of Hybrid learning itself. The research approach used is qualitative research. The research method uses descriptive and quantitative methods. Data collection techniques using observation, deepening, and documentation techniques. Data analysis through data reduction, data presentation, and verification. Checking the validity of the data using the methods of credibility, conformability, transferability, and dependability. As a result, Nurul Jadid University has a shift system, a week of studying offline and at school. The weakness is that students are less active in delivering responses in WhatsApp groups, and the practice of copy-pasting daring assignments among students is increasingly widespread. Implications show that Hybrid learning requires the agility of students and lecturers so that learning can take place optimally.